Peran Manajemen Pendidikan dalam Pengembangan Kurikulum PAI di SMAN 14 Sukawening Garut - Erlang Darma Kusuma; Masripah; Fiqra Muhamad Nazib; Yufi Mohammad Nasrullah (Advances In Education Journal, 2026)
Educational management plays a strategic role in ensuring the success of Islamic Religious Education (PAI) curriculum development in educational institutions. This study aims to analyze the role of educational management in PAI curriculum development at SMAN 14 Sukawening Garut, encompassing aspects of curriculum planning, organizing, implementation, and evaluation. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation study, with key informants consisting of the principal, PAI teachers, and the curriculum team. Data analysis was conducted using Miles and Huberman's interactive analysis model through the stages of data reduction, data display, and conclusion drawing. The findings reveal that educational management at SMAN 14 Sukawening Garut plays a determinant role across all stages of PAI curriculum development, in which the active involvement of the principal, PAI teachers, and the curriculum team constitutes a key factor in ensuring the curriculum's relevance to students' needs. Nevertheless, structural constraints were identified, including limited educational resources, insufficient teacher training programs, and the absence of a comprehensive and systematic curriculum evaluation mechanism. This study proposes a Collaborative Adaptive PAI Curriculum Management Model resting on three pillars: participatory multi-stakeholder collaboration, contextual curriculum adaptivity, and continuous managerial capacity building for educators. These findings contribute to curriculum management theory by recognizing that structural constraints function as moderating variables that significantly affect curriculum development effectiveness, particularly in schools located in resource-limited regions.